2003
DOI: 10.1161/01.hyp.0000085650.29823.f2
|View full text |Cite
|
Sign up to set email alerts
|

Role of COX-2 in the Enhanced Vasoconstrictor Effect of Arachidonic Acid in the Diabetic Rat Kidney

Abstract: Abstract-In the rat isolated perfused kidney, arachidonic acid elicits cyclooxygenase-dependent vasoconstriction through activation of PGH 2 /TxA 2 receptors; responses are enhanced in kidneys from diabetic rats. This study examined the roles of cyclooxygenase-1/cyclooxygenase-2 in the enhanced renal vasoconstrictor effect of arachidonic acid in streptozotocin-diabetic rats. Release of 20-HETE was also determined, as this eicosanoid has been reported to elicit cyclooxygenase-dependent vasoconstriction. We conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 28 publications
9
40
2
1
Order By: Relevance
“…Harris' group reported that chronic administration of a COX-2 inhibitor to hypertensive diabetic rats reduced the appearance of markers for renal damage, suggesting that increased COX-2 may be an early step in the development of nephropathy (Cheng et al, 2002). We confirmed the increase in the renal cortical expression of COX-2 in untreated STZ-diabetic rats and showed that a COX-2 inhibitor reduced the enhanced endoperoxide-mediated renal vasoconstrictor response to AA as well as the enhanced associated release of prostaglandins that we had reported for the diabetic rat (Quilley and McGiff, 1990;Quilley and Chen, 2003).…”
supporting
confidence: 86%
“…Harris' group reported that chronic administration of a COX-2 inhibitor to hypertensive diabetic rats reduced the appearance of markers for renal damage, suggesting that increased COX-2 may be an early step in the development of nephropathy (Cheng et al, 2002). We confirmed the increase in the renal cortical expression of COX-2 in untreated STZ-diabetic rats and showed that a COX-2 inhibitor reduced the enhanced endoperoxide-mediated renal vasoconstrictor response to AA as well as the enhanced associated release of prostaglandins that we had reported for the diabetic rat (Quilley and McGiff, 1990;Quilley and Chen, 2003).…”
supporting
confidence: 86%
“…This model allows the accurate control of regional hemodynamic variables such as perfusion pressure and flow intensity, as well as the elimination of neurohumoral and blood cell influences on renal function. Actually, the model of the isolated kidney perfused at constant flow with salt solutions has been demonstrated to be a valuable tool for the study of the regulation of renal vascular tone (2,42,52,57). Using this experimental setup, we demonstrated for the first time that exercise training of moderate intensity increases vasodilation of whole renal circulation elicited by endothelium-dependent and -independent vasodilating agents.…”
Section: Exercise Training and Renal Vascular Reactivitymentioning
confidence: 96%
“…Hyperglycemia-induced ROS production (in the mitochondria) occurs in endothelial cells and in platelets through auto-oxidation of glucose [Wolff and Dean, 1987], advanced glycation end (AGE) product formation and the binding of AGEs to their receptors [Yan et al, 1994;Ceriello, 1999], increased substrate flux through the polyol pathway [Giugliano et al, 1996], and/or through stimulation of the eicosanoid metabolic pathways [Tesfamariam and Cohen, 1992a,b;Quilley and Chen, 2003]. The major sources of O 2 À in cardiovascular cells are: NADH/NADPH oxidase [Griendling et al, 2000], which transfers electrons from NADH or NADPH to molecular oxygen, producing O 2 À ; xanthine oxidase [Wolin, 1996]; endothelial nitric oxide synthase [Ignarro et al, 1999]; cyclooxygenase-2 [Adeagbo et al, 2003]; myeloperoxidase [Berliner and Heinecke, 1996]; and lipoxygenases [Kunsch and Medford, 1999].…”
Section: Oxidative Stress and Diabetesmentioning
confidence: 99%